Personality Traits and Their Validity in Predicting Job Performance at Recruitment: a Review - Alhendi, Osama (International Journal of Engineering and Management Sciences, 2019)
One of the most critical challenges human resources management usually faces is the procedure of recruitment and selection. At the recruitment, the factor of qualification is very important. However, HR management should take into account the personality of the candidate. For example, most of the companies’ profits rely on the performance of the frontline employee and their behavior toward the customer. Therefore, HR management usually uses the assessment of personality and integrity. Based on the literature, there is a correlation between personality traits and job performance. This study is a literature review analysis which contains previous studies in regard to the of Big Five Factors at the recruitment and their validity in predicting employee’s performance in the firm.